HOUSING AFFORDABILITY AMONG CIVIL SERVANTS IN OGUN STATE, NIGERIA - Mendie, Ethel Asinya; Sakariyau, Jamiu Kayode (FUDMA JOURNAL OF SCIENCES, 2023)
Housing has been acknowledged generally as a key human necessity. One of its problems may be claimed that it is not affordable for the ordinary Nigerian worker, whose earnings and wages are now strongly depressed and unable to fulfill their fundamental necessities. From the perspective of the above, this study studied the affordability of government workers in Ogun State, Nigeria. Purposive method of sampling was used to sample two government agencies and parastatals. A total of One Hundred and Ten (110) government officials were picked. 94 questionnaires were returned. The necessary data was gathered using the questionnaire, which was then, analyzed using descriptive and medium item score statistics. The results showed that, on average, government workers in Ogun State could afford to pay their rent because most of them, particularly those in the medium and high income brackets, spend less than 30% of their annual salary on housing. Public and private engagements were suggested in the study as a method of providing state housing that is both inexpensive and sustainable.